2003
DOI: 10.1385/bter:91:3:193
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zinc Levels During Pregnancy and Its Relationship to Maternal and Neonatal Characteristics: A Longitudinal Study

Abstract: Forty consecutive healthy pregnant women aged 17-38 yr who attended the antenatal clinic of the Department of Obstetrics and Gynecology, Ankara University in their first trimester participated in the study. The pregnant women were followed up longitudinally until the end of their pregnancy. Forty healthy age-matched nonpregnant women were used as a control group. Each pregnant woman was interviewed and a special questionnaire recording dietary history (3-d recall) and socioeconomic status (SES) was used. Birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
2
11
1
Order By: Relevance
“…In conclusion, findings of this longitudinal study on plasma Zn levels were found to be similar to our previous cross-sectional and longitudinal studies [2,3,8]. Similar changes could not be observed for hair Zn concentrations probably as a result of the fact that all pregnant women were from Ankara rather than from villages, where the dietary habit is frequently associated with zinc deficiency [2,8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In conclusion, findings of this longitudinal study on plasma Zn levels were found to be similar to our previous cross-sectional and longitudinal studies [2,3,8]. Similar changes could not be observed for hair Zn concentrations probably as a result of the fact that all pregnant women were from Ankara rather than from villages, where the dietary habit is frequently associated with zinc deficiency [2,8].…”
Section: Discussionsupporting
confidence: 87%
“…It has been demonstrated by several experimental and human studies that Zn deficiency may result in adverse maternal and fetal consequences [1,4À6]. Our previous cross-sectional and longitudinal studies on serum or plasma Zn concentrations revealed low Zn levels, particularly in poorly nourished pregnant Turkish women [2,3,7,8]. Zn status of pregnant women has usually been assessed by measuring serum/plasma Zn or erythrocytes, leukocytes, and hair Zn concentrations [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Aydemir et al showed that there were significant differences between plasma zinc levels among mothers of different socioeconomic status. Moreover, they did not find any relationship between plasma zinc levels and infant anthropometric parameters [19]. Maternal nutritional needs increase during pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…Although it is increasingly acknowledged that societal factors play a significant role in micronutrient status and pregnancy outcomes (1, 3), studies on impacts of socioeconomic status on pregnancy outcomes have produced conflicting results (4, 5). For instance, the risk of preterm birth has been reported in mothers of low socioeconomic status (6).…”
Section: Introductionmentioning
confidence: 99%